The Use of Claim Resources by Undergraduate Students in High- and Low-Graded Persuasive Essays - Sook Hee Lee (Cranmore Publishing, 2019)
This paper compares high-graded essays to low-graded essays in terms of various 'Claims' resources used by undergraduate students. The theoretical basis of the Claim is mainly derived from the ENGAGEMENT system of the appraisal theory within a Systemic Functional Linguistics (SFL) framework. The ENGAGEMENT system is concerned with how writers engage with readers through internal voices of Averral and external voices of 'Attribution'. Data was collected from 12 persuasive essays written by both international and local Australian students enrolled in an EAP course running at a regional university in Australia. The text analyses reveal significant differences between high-graded essays and low-graded essays in using Claim resources. While successful writers can produce essays that display a balanced incorporation of strategies of internal Averral into their presentation of external Attribution within particular schematic stages, poor writers fail to display the pattern. Pedagogical implications will be discussed in terms of academic literacy and integrity.